Progressive ontogenetic niche shift over the prolonged immaturity period of wandering albatrosses. Issue 10 (11th October 2017) - Carravieri, Alice; Weimerskirch, Henri; Bustamante, Paco; Cherel, Yves
Abstract : Very little is known about trophic ontogenetic changes over the prolonged immaturity period of long-lived, wide-ranging seabirds. By using blood and feather trophic tracers (δ 13 C and δ 15 N, and mercury, Hg), we studied age-related changes in feeding ecology during the immature phase of wandering albatrosses Diomedea exulans when they gradually change from a pure oceanic life to visits to their future breeding grounds. Immatures fed in subtropical waters at high trophic positions during moult. Between- and within-individual variations in isotopic niche were very high, irrespective of age, highlighting wide-ranging exploratory behaviours. In summer, while acting as central-place foragers from their future breeding colony, individuals progressively relied on lower trophic level prey and/or southern latitudes as they aged, until occupying a similar isotopic niche to that of adults. Immatures had exceptionally high Hg burdens, with males having lower Hg concentrations than females, suggesting that they foraged more in subantarctic waters. Our findings suggest a progressive ontogenetic niche shift during central-place foraging of this long-lived species.